Pengelolaan, Tugas dan Fungsi Badan Permusyawaratan Desa (BPD) - Ifrani Ifrani (UIN Antasari Banjarmasin, 2022)
AbstractThe Village Consultative Body (BPD) is an institution that embodies democracy in the administration of village governance. The BPD can be considered as the